The m6A regulators in prostate cancer: molecular basis and clinical perspective - Cao, Yu; Jia, Man; Duan, Chunyan; Yang, Zhihui; Cheng, Bo; Wang, Ronghao (Frontiers in Pharmacology, 2024)
Prostate cancer (PCa) is the second leading cause of cancer-related death among men in western countries. Evidence has indicated the significant role of the androgen receptor (AR) as the main driving factor in controlling the development of PCa, making androgen receptor inhibition (ARI) therapy a pivotal management approach. In addition, AR independent signaling pathways also contribute to PCa progression. One such signaling pathway that has garnered our attention is N6-Methyladenosine (m6A) signaling, which refers to a chemical modification on RNA with crucial roles in RNA metabolism and disease progression, including PCa. It is important to comprehensively summarize the role of each individual m6A regulator in PCa development and understand its interaction with AR signaling. This review aims to provide a thorough summary of the involvement of m6A regulators in PCa development, shedding light on their upstream and downstream signaling pathways. This summary sets the stage for a comprehensive review that would benefit the scientific community and clinical practice by enhancing our understanding of the biology of m6A regulators in the context of PCa.